Pengaruh Pembelajaran IPAS Dengan Model Project Based Learning Berbantuan Media Robot Education Box Terhadap Kemampuan Berpikir Kreatif Siswa Kelas VI - Elpa Meilanda, Nadia; Widi Winarni, Endang; Gumono (Jurnal Kajian Pendidikan Dasar, 2025)
The purpose of this research is to analyze the influence of IPAS learning using the Project Based Learning model assisted by the Robot Education Box media on the ability to think fluently, flexibly, and originally. The type of research used is quasi-experimental research employing a pretest-posttest control group design. The type of data used is quantitative data, utilizing a questionnaire instrument and expert validation sheets. Based on the research results, it was found that the implementation of IPAS learning using the Project Based Learning model assisted by the Robot Education Box media has a significant effect on fluency thinking skills. This is demonstrated by the average posttest score for fluent thinking ability in the control class, which is 37. Meanwhile, the average score for the experimental class is 88. The implementation of IPAS learning using the Project Based Learning model assisted by the Robot Education Box media has a significant impact on flexible thinking ability. This is shown by the average posttest score of flexible thinking ability in the control class being 28, while the average score in the experimental class is 71. The implementation of IPAS learning using the Project Based Learning model assisted by the Robot Education Box media has a significant impact on original thinking ability. This is shown by the average posttest score of fluent thinking ability in the control class, which is 33. The result of the correlation test shows that the flexibility and originality ability is 0.013, concluding that there is a significant relationship.